The Joined Destiny of Migration and European Citizenship - Nadia Urbinati (Rosenberg & Sellier, 2015)
In this paper I try to unpack the nest of issues that recent waves of migrations bring to the floor and show how immigration plays a crucial role in the making or unmaking democratic citizenship in post-national Europe. Although recurrent terrorist attacks make harder and harder for many opinion-makers and ordinary citizens to associate immigration with positive opportunity for European citizenship, the paper argues that the right to free movement and of emigration is embedded in the nucleus of principles and ideals that makes for European citizenship since the Treaty of Rome. Subsequently, the paper introduces the category of statelessness and uses it to tackle the problem of the legal and political evolution furthered by the practice of rights within the horizon that is defined by the ideal of a European post-national citizenship. Refugees and immigrants are interpreted as a challenge and an opportunity in the spirit of Hannah Arendt’s intuition that citizenship brings to the floor an unsolvable paradox between the human and the political. The conclusion of the paper argues that stateless people—the migrants—personify this paradox as they can be the locus of a new political practice that signals an incipient form of citizenship, truly disconnected from the nation as the European citizenship aspires to be. The denial of many civil and political rights to undocumented immigrants and the detention of thousands of migrants in the camps located at the peripheries of Europe contrast radically with the community of rights that Europe has sought to be since its inception.